2008
DOI: 10.1080/00365520701679264
|View full text |Cite
|
Sign up to set email alerts
|

Early renal function post-liver transplantation is predictive of progressive chronic kidney disease

Abstract: GFR levels below 30 ml/min/1.73 m2 at 3 months post-liver transplantation are associated with the development of later CKD Stage 4-5 long after liver transplantation. The importance of this finding is the possibility of identifying at an early stage those individuals that may benefit from early implementation of calcineurin sparing or a withdrawal regimen with the goal of preserving long-term renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 17 publications
1
30
0
2
Order By: Relevance
“…This relationship was also noted by other authors [33]. Various investigators have found by univariate analysis a significant relationship between pre-transplant kidney dysfunction and chronic kidney disease in their series of LT recipients [34][35][36]. Stratified analysis on various subgroups of interest showed that the link between pre-transplant kidney function and chronic kidney disease among liver transplant recipients was particularly evident in the subset of observational studies which estimated glomerular filtration rate (instead of serum creatinine alone) before liver transplant.…”
Section: Discussionsupporting
confidence: 70%
“…This relationship was also noted by other authors [33]. Various investigators have found by univariate analysis a significant relationship between pre-transplant kidney dysfunction and chronic kidney disease in their series of LT recipients [34][35][36]. Stratified analysis on various subgroups of interest showed that the link between pre-transplant kidney function and chronic kidney disease among liver transplant recipients was particularly evident in the subset of observational studies which estimated glomerular filtration rate (instead of serum creatinine alone) before liver transplant.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, renal failure is leading to prolonged hospital stay, increased rate of rejection and rate of infection in liver transplant recipients [8]. There are many reports regarding preoperative renal function, especially the role of preoperative creatinine serum levels in post-operative outcomes in liver transplant recipients [12-14]. …”
Section: Introductionmentioning
confidence: 99%
“…In den Jahren nach der Transplantation entwickelt sich bei vielen Patienten (30-50 %) eine chronische Niereninsuffizienz, mit Dialysepflichtigkeit in 5-20 % der Fälle [13,23,24,36]. Die Häufigkeit variiert je nach transplantiertem Organ und wird zu einem signifikanten Anteil auch von der Grundkrankheit mitbestimmt.…”
Section: Renale Ko-morbidität Nach Transplantation Solider Organeunclassified